2018
DOI: 10.5114/ceji.2018.81353
|View full text |Cite
|
Sign up to set email alerts
|

Complete blood count-derived inflammatory markers in adolescents with primary arterial hypertension: a preliminary report

Abstract: Aim of the studyThe aim of our study was to evaluate selected inflammatory markers in children with untreated primary hypertension and to establish the relation between inflammatory markers and 24-hour ambulatory blood pressure monitoring (ABPM) and clinical and biochemical parameters.Material and methodsIn 54 children (15.12 ±2.02 years) with untreated primary hypertension, with excluded overt inflammation, we evaluated: neutrophils (NEU; 1000/μl), lymphocytes (LYM; 1000/μl), platelets (PLT; 1000/μl), mean pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 32 publications
(51 reference statements)
1
16
0
Order By: Relevance
“…There was no significant association between LMR and early pregnancy outcome at the range of more than 2. 19. The blood routine examination is a easily measurable and available method to reflect the general inflammatory status [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant association between LMR and early pregnancy outcome at the range of more than 2. 19. The blood routine examination is a easily measurable and available method to reflect the general inflammatory status [21].…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR) and lymphocytemonocyte ratio (LMR) are a series of new parameters derived from complete blood counting reflecting inflammatory status. Because of its availability and extensive use, accumulating studies have been reported that these inflammation-related parameters are pretty relative with the prognosis and genesis of many diseases [19,20]. Therefore, we sought to evaluate the associations of aforementioned indexes and the early pregnancy outcome in women with early threatened abortion.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, a vast number of studies have implicated endothelial dysfunction in the progression of atherosclerosis and target organ damage in primary hypertension [3, 6, 7]. Several biomarkers have been established to reflect the status of subclinical inflammation in cardiovascular diseases, including high-sensitivity C-reactive protein (CRP), interleukin (IL)-6, and complete blood count-derived indices [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that NLR is elevated and related to poor clinical outcomes of cardiovascular disease in adults, including acute coronary syndrome, atherosclerosis, and heart failure [28][29][30]. However, few studies have looked at NLR levels in children with newly diagnosed hypertension [13,31]. In the current study, we found the neutrophil counts and NLR were signi cantly higher in hypertension children than healthy children, and the elevated NLR may re ect the upregulation of overall in ammatory and stress status in these children.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Skrzypczyk and colleagues reported NLR correlated with 24-hour ambulatory mean arterial pressure levels in adolescent [13], which suggest that blood cell parameter may also be useful in pediatrics population. To date, no studies have investigated the possible link between NLR and target organ damage in hypertension children.…”
Section: Introductionmentioning
confidence: 98%